Development of three fusarium crown rot causal agents and systemic translocation of deoxynivalenol following stem base infection of soft wheat. (12th February 2018) - Beccari, G.; Prodi, A.; Pisi, A.; Nipoti, P.; Onofri, A.; Nicholson, P.; Pfohl, K.; Karlovsky, P.; Gardiner, D. M.; Covarelli, L.
Abstract : Fusarium pseudograminearum, F. culmorum and F. graminearum are the most important fusarium crown rot (FCR) causal agents. They have the common ability to biosynthesize deoxynivalenol (DON). To elucidate the behaviour of each of the three species, a comparative study was carried out to investigate symptom progression, fungal systemic growth and translocation of DON following stem base inoculation of soft wheat. FCR symptoms were mainly localized in the inoculated area, which extended up to the second node for all inoculated species. Only the most aggressive strains caused symptoms up to the third node. Real‐time quantitative PCR showed that fungal colonization reached the third node for all the tested species, but a low percentage of plants showed colonization above the third node following inoculation with the most aggressive strains. Fungal growth was detected in symptomless tissues but none of the three species was able to colonize as far as the head tissues. However, even if the pathogens were not detected in the heads, DON was detected in head tissues of the plants inoculated with the most aggressive strains. These results demonstrate that F. pseudograminearum, F. culmorum and F. graminearum, under the same experimental conditions, follow a similar pattern of symptom progression, fungal colonization and DON translocation after stem base infection. Differences in the extent of symptoms, fungal colonization and mycotoxin distribution were mainly attributable to strain aggressiveness. These findings provide comparative information on the events following infection of the stem base of wheat by three of the most important FCR casual agents.